IBM PowerHA SystemMirror for i. - Granum, David; Grygierczyk, Edward; Jordan, Sabine; Mayhew, Peter; Painter, David (IBM redbooks., 2016)
IBM® PowerHA® SystemMirror® for i is the IBM high-availability (HA), disk-based clustering solution for the IBM i operating system. When PowerHA for i is combined with IBM i clustering technology, PowerHA for i delivers a complete HA and disaster-recovery (DR) solution for business applications that run in an IBM i environment. With PowerHA for i, you can support HA capabilities with either native disk storage, IBM DS8000® storage servers, or IBM Storwize® storage servers. This IBM Redbooks® publication helps you to install, tailor, and configure IBM PowerHA SystemMirror for i with the IBM System Storage® DS8000 series. This publication provides you with planning information to prepare to use the various PowerHA offerings for the IBM DS8000 family. It also provides implementation and management information. It provides guidance about troubleshooting these solutions and identifies the documentation and data that you need to capture before you call IBM Support. This book is part of a four-book volume set that gives you a complete understanding of PowerHA for i that uses native disk storage, IBM DS8000 storage servers, or IBM Storwize storage servers. The following IBM Redbooks publications are part of this PowerHA for i volume set: IBM PowerHA SystemMirror for i: Preparation, SG24-8400 IBM PowerHA SystemMirror for i: Using IBM Storwize, SG24-8402 IBM PowerHA SystemMirror for i: Using Geographic Mirroring, SG24-8401 Important: The information that is presented in this volume set is for technical consultants, technical support staff, IT architects, and IT specialists who are responsible for providing HA and support for IBM i solutions. If you are new to HA, review the information that is presented in the first book of this volume set, IBM PowerHA SystemMirror for i: Preparation (Volume 1 of 4), SG24-8400, to get a general understanding of clustering technology, independent auxiliary storage pools (IASPs), and the PowerHA architecture.